Improving Memorization of The Qur'an and Hadith Through Inspiration Method Among Students at Madrasah Aliyah - Zulkarpian Zulkarpian; Moch. Tolchah; Din M. Zakariya (Eduvest - Journal of Universal Studies, 2024)
Al-Quran Hadith is a mandatory lesson and is given continuously at MI, MTs, and MA to motivate students to practice the values contained in the Al-Qur'an and the Prophet's hadith in everyday life. The facts show that the completion score for Al-Quran Hadith lessons is still low, especially because students have difficulty memorizing verses from the Koran and Hadith. This research aims to describe the increase in memorizing verses and hadiths in the Al-Quran Hadith subject through the ILHAM Method in class XI Madrasah Aliyah students. This research uses a qualitative approach with descriptive data analysis. The research data sources were Al-Quran Hadith subject teachers and 19 students in class XI MAN 1 Simeulue. Data collection is carried out through observation, interviews or interviews, and documentation. Data validity testing was carried out through the triangulation method. Next, the data is analyzed through data reduction, data display, and verification. The results of the research show that the application of the ILHAM (Integrated, Listening, Hand, Attention, and Matching) method in the Al-Quran Hadith subject can improve the ability to memorize Al-Quran verses and Hadith in class XI Madrasah Aliyah students.